2020
DOI: 10.1016/j.eneco.2020.104736
|View full text |Cite
|
Sign up to set email alerts
|

Objective vs. subjective fuel poverty and self-assessed health

Abstract: Policies towards fuel poverty often use relative or absolute measures. The effectiveness of the official indicators in identifying fuel poor households and assessing its impact on health is an emerging social policy issue. In this paper we analyse objective and perceived fuel poverty as determinants of selfassessed health in Spain. In 2014, 5.1 million of her population could not afford to heat their homes to an adequate temperature. We propose a latent class ordered probit model to analyse the influence of fu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
46
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 135 publications
(54 citation statements)
references
References 68 publications
5
46
0
Order By: Relevance
“…There are also two indicators based on self-reporting household conditions, namely the "EU survey on income and living conditions" and the "Survey on perceptions and statements from households" [13]. Finally, it should be noted that energy or fuel poverty may change, based on subjective and objective measurements, and may lead to different results, as reported by Price et al [41] and Llorca et al [42].…”
Section: Methodsmentioning
confidence: 99%
“…There are also two indicators based on self-reporting household conditions, namely the "EU survey on income and living conditions" and the "Survey on perceptions and statements from households" [13]. Finally, it should be noted that energy or fuel poverty may change, based on subjective and objective measurements, and may lead to different results, as reported by Price et al [41] and Llorca et al [42].…”
Section: Methodsmentioning
confidence: 99%
“…Whilst the measurement of fuel poverty remains somewhat contested ( Deller et al, 2021 ; Thomson, 2020 ), recent literature has drawn upon the strengths of objective and subjective approaches by employing both sets of indicators (see e.g. Awaworyi Churchill et al, 2020 ; Kahouli, 2020 ; Llorca et al, 2020 ; Awaworyi Churchill and Smyth, 2021 ). The seminal work of Waddams Price et al (2012) evaluates the positive yet complex overlap between official objective indicators and subjective indicators.…”
Section: Methodsmentioning
confidence: 99%
“…In the literature, human capital accumulation is argued as one of the main drivers of productivity (Chang et al 2016 ), while EP is found to have negative impacts on people’s living standards, health, and income (Chevalier and Ouédraogo 2009 ; Llorca et al 2020 ). Thus, EP may lead to a deterioration in human capital since people have to spend more time collecting basic materials for living (Chevalier and Ouédraogo 2009 ).…”
Section: Literature Review and Hypothesis Constructionmentioning
confidence: 99%
“…Most detrimentally, EP is documented as the cause of degradation of individual well-being and health (e.g. see Kose ( 2019 ), Llorca et al ( 2020 )). Recently, Amin et al ( 2020 ) find that EP causes a decrease in economic development in both the short- and long-run in a sample of seven South Asian countries from 1995 to 2017.…”
Section: Introductionmentioning
confidence: 99%